PRODUCT POSITIONING AND BRANDING - Agus Hasan Pura A (Bina Ekonomi, 2009)
The goal of a positioning strategy is to create a product-price position attractive to target customers and good source of cash  flow  for the business.  Product Positioning is at the core of every strong brand. A distinct and well - understood association exists between such a brand and its primary customer  benefit. How it will create differentiated value for targeted segments and what position it want to occupy  in those segments. Product positioning strategies are based on product differentiation, service differentiation and brand differentiation.  Total benefits derived from this positioning must be larger  than total cost of obtaining  these benefits. Customers are influence by the status of a brand name or by the assurance of a well-known company (Lexus & Mercedes have strong brand association with prestige or status). A strong brand enhances positive evaluation; maintain a high of product awareness & provides a consistent image or brand personality;